The potential of BASF NPK fertilizers associated with Trichoderma viride fertilizer on the growth and production of shallots (Allium ascalonicum L.) - Savitri Savitri; Usnawiyah Usnawiyah (Journal of Tropical Horticulture, 2019)
This research was carried out on the Experimental Garden, Faculty of Agriculture, Abulyatama University, Aceh Besar. This research was conducted from September 26th to December 2nd, 2017. This research was assigned in a Completely Randomized Design (CRD) factorial with 3 replications. There were 12 combinations of treatments and 36 units of experiments. The first factor was Trichoderma viride Fertilizer (T) which consists of 4 levels: T0 = 0 gram/polybag, T1=50 g/polybag, T2=100 g/polybag, T3=150 g/polybag. The second factor was BASF NPK Fertilizers (N) consists of 3 levels: N = 0 g/polybag, N1=3 g/polybag, N2=6 g/polybag. The parameters observed in this study were plant height, bulb diameter, wet weight and dry weight of bulbs. The results revealed that various doses of T. viride fertilizer increased the plant height respectively at 20 and 40 days after planting. Surprisingly, there was no significant difference in plant height at 60 days after planting. The best results for the application of T. viride fertilizer were found in T1 (50 g/polybag). This fertilizer also exhibited insignificant results in bulb diameter, wet weight and dry weight of bulbs at all observed ages. The application of BASF NPK fertilizers did not significantly affect all observed parameters (plant height, bulb diameter, wet weight and dry weight of onion bulbs). There were no interactions due to application of T. viride fertilizer and BASF NPK fertilizers to all observed parameters.